Identification of Suitable Biomass Torrefaction Operation Envelops for Auto-Thermal Operation - Yun, Huimin; Wang, Ziliang; Wang, Ruixu; Bi, Xiaotao; Chen, Wei-Hsin (Frontiers in Energy Research, 2021)
Auto-thermal operation of biomass torrefaction can help avoid additional heat investment and the associated costs to the system. This work provides a general method for relating the feedstock-specific parameters to the energy balance and pre-diagnosing the potential of auto-thermal for different biomass torrefaction and pyrolysis systems. Both solid and gas thermal properties under various torrefaction conditions and their influences to the torrefaction system energy balances are considered. Key parameters that influence the process auto-thermal operation are analyzed, which include torrefaction reaction heat, torrefaction conditions, drying method, biomass species, and inert N2 flowrate. Equations of torgas and biomass higher heating values (HHVs), as well as the torrefaction reaction heat at different operating conditions are developed. It is found that torgas and biomass HHVs increase with torrefaction temperature and biomass weight loss. Torrefaction reaction heat has a linear relationship with the biomass weight loss, with a positive slope at 250–260°C, and a negative slope at 270–300°C, which indicates that torrefaction shifts from endothermic to exothermic at ∼270°C. Applying advanced drying technology and avoiding the use of N2 can help the system achieve auto-thermal operation at lower torrefaction temperature and residence time, thus leading to a higher process energy efficiency and product yield. This is the first work to relate the micro level element changes of biomass to the macro level process energy balances of the torrefaction system. This work is important in design and operation of the torrefaction system in both pilot and industrial scales to improve process efficiency and predict product quality in a reliable and economic manner.